Information System Point of Sales Based Real Time on PT. Buccheri Indonesia - Teofilus Sunarsa; Paulus Yayan Christian; Yuki Gunawan (Komunitas Dosen Indonesia, 2020)
Buccheri is a retail company that provides quality footwear for men and women since 1980. We begin our history with our first flagship store in a historic business district,